The heart of business leadership principles for the next era of capitalism - Joly, Hubert 1959-; Lambert, Caroline 1970- (Harvard Business Review Press, 2021)
Part I. The meaning of work: Adam's curse -- Why we work -- The problem with perfection -- Part II. The purposeful human organization: The tyranny of shareholder value -- The business of building cathedrals -- Putting a noble purpose to work -- How to turn around a business without everyone hating you -- Part III. Unleashing human magic: Moving past carrots and sticks -- Ingredient #1, connecting dreams -- Ingredient #2, developing human connections -- Ingredient #3, fostering autonomy -- Ingredient #4, achieving mastery -- Ingredient #5, putting the wind at your back -- Part IV. The case for purposeful leadership: How we lead matters -- The purposeful leader -- A call for action
Includes index
Keywords: Best Buy (Firm); Führungskräfte / (DE-627)091361532 / (DE-STW)11302-1; Führungsstil / (DE-627)091361583 / (DE-STW)15825-5; Unternehmensethik / (DE-627)091396506 / (DE-STW)18116-5; Business ethics; Industrial management; Psychology, Industrial; Leadership; Success in business